Letter (copy) - Tewson, Vincent
1939-07-20 038-0079-002 -2- I promised I would drop you a personal note to see how far you feel you could respond to such a request in view of your many other interests. Yours sincerely, Assistant Secretary. 292/946/38/79(II)